PO 35 - ANESTESIA NA FRATURA DO COLO DO FÉMUR - UMA AUDITORIA CLÍNICA - Sancha Andrade Oliveira Costa Santos1; Helena Maria Ferreira da Silva1; Joaquim Maria Rafael de Borba1; Rui Freitas Mendonça Correia Silva1; António Armando Furtado Paiva1; Cecília Gomes Pinto Amarante Dias1 (Journal of the Portuguese Society of Anesthesiology, 2023)
.